Investigation of The Relationship Between Misconceptions and Answering Behaviors on The Example of The Mathematical Literacy - Emre Kucam; Ergül Demir (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
The aim of this research was to determine the relationship betweenconceptual misconceptions in math literacy skills of secondary school eighthgrade students and their answering behaviors which they used in responding toquestions. This is a correlational research. The sample of the researchconsists of 340 students who are educated in the eighth grades of three schoolsin the provinces of Çankaya, Etimesgut and Yenimahalle in Ankara. PersonalInformation Form and Two-Tier Diagnostic Test were used in order to determinethe conceptual misconceptions of students in mathematical literacy and theResponsive Behavior Form was used to determine which behavior was used torespond to the answers. All these tools were developed by the researcher tocollect information about the students. In the analysis of the data obtainedfrom the research, descriptive statistics and chi-square analysis were used.According to research findings; the students who have misconceptions mostlyused elimination answering behaviors and the students who do not havemisconceptions used calculation and elimination behaviors. When answeringbehaviors are analyzed according to the types of misconceptions, it isdetermined that the random marking is the most used in the type ofover-specialization misconceptions and in the case of the other misconceptionstypes, the most random marking answering behaviors are used. Furthermore, itwas determined that the types of misconceptions and answering behaviors did notdiffer according to the gender, and that the answering behavior of the studentsdid not differ according to the city they were in.